2021
DOI: 10.1021/acsami.1c15358
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate-Modified Nanoceria with Multiantioxidant Enzyme-Mimetic Activity for Reactive Oxygen Species/Reactive Nitrogen Species Scavenging from Cigarette Smoke

Abstract: Highly toxic radicals including reactive oxygen species (ROS) and reactive nitrogen species (RNS) in cigarette smoke play an important role in oxidative damage of the lungs, which cannot be efficiently scavenged by current filter techniques. Herein, a novel alendronate-coated nanoceria (CeAL) nanozyme is explored for cigarette filter modification for ROS/RNS scavenging. The CeAL nanozyme with an adjustable oxidation state and high thermal stability exhibits an excellent superoxide dismutase (SOD)-like activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…48 In addition, multiple studies have demonstrated better stability (in a wider range of pH and working temperature) and multiple ROS scavenging ability of nanoceria versus natural enzymes such as SOD and CAT. 28,49 Furthermore, compared with other CeO 2 nanoparticles, 23,32,50 CeO 2 @BSA nanoclusters possessed the smallest average size and better ROS scavenging ability (Supplementary Table 2). All these comparisons indicate excellent catalytic property to remove multiple ROS.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…48 In addition, multiple studies have demonstrated better stability (in a wider range of pH and working temperature) and multiple ROS scavenging ability of nanoceria versus natural enzymes such as SOD and CAT. 28,49 Furthermore, compared with other CeO 2 nanoparticles, 23,32,50 CeO 2 @BSA nanoclusters possessed the smallest average size and better ROS scavenging ability (Supplementary Table 2). All these comparisons indicate excellent catalytic property to remove multiple ROS.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…X-ray photoelectron spectroscopy (XPS) analyses were used to determine the surface Ce 3+ /Ce 4+ ratio on the surface of the CeO 2 @PAA@RGD nanoparticles. Two main peaks, including Ce 3d 3/2 and Ce 3d 5/2, in the Ce 3d spectrum of CeO 2 @PAA@RGD are presented in Figure 1 e. The Ce 3d spectrum was decomposed into six peaks [ 49 ], including four peaks of Ce 4+ and two peaks of Ce 3+ [ 41 ]. The peaks of Ce 3+ are 881.90 and 900.60 eV, while the peaks of Ce 4+ at 885.30, 904.00, 887.10, and 906.30 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxyl radicals (·OH) scavenging assay was performed according to the report by Zhou et al [ 41 ]. ·OH was produced by the Fenton reaction: H 2 O 2 + Fe 2+ = ·OH + H 2 O + Fe 3+ .…”
Section: Methodsmentioning
confidence: 99%
“…39 The H 2 O 2 scavenging effect of PBNPs was examined by mixing H 2 O 2 (500 μM) and PBNPs (12.5, 25, 50, 100, and 200 μg/mL), with the residual H 2 O 2 levels in the supernatant being measured using a hydrogen peroxide assay kit and a microplate spectrophotometer by assessing absorbance examined at 562 nm. Hydroxyl radicals (•OH) elimination assay was conducted according to the report by Zhou et al 40 •OH in aqueous solution was generated through the Fenton reaction by adding FeSO 4 (0.4 mM) and H 2 O 2 (0.4 mM) into PBS (0.1 M, pH 7.4) at 37 °C. Then, different concentrations of PBNPs were added into the solution, followed by adding a salicylic acid (SA) indicator (2 mM) to detect the remaining •OH.…”
Section: Methodsmentioning
confidence: 99%